Use of Microalgae for Biodiesel Production (Research, Society and Development, 2018)
Most of society's energy demands are still met by fossil fuels. However, this source has been replaced by other renewable, less aggressive to the environment and with better cost / benefit.As an example, we can mention biofuels produced from oil plants and microorganisms, which are capable of replacing petroleum derivatives with equivalent efficiency. Thanks to its high production of lipids, microalgae, whose diameter does not exceed 2 mm, are studied and are being applied in the production of biofuels, especially biodiesel, and about 150 microalgae species are used commercially. The objective of this paper was to carry out a literature review on the production of biodiesel from microalgae. This study is of the theoretical-conceptual type, since it was elaborated from the researches in the national and international literature on the production of biofuels from microalgae, besides the consultation to governmental organs and pertinent legislations. In addition, it intends to present the main techniques of cultivation and production, as well as the main advantages and disadvantages of the use of microalgae for biodiesel production. From environmental problems and the reduction of fossil reserves, it is necessary to invest in alternative sources, and biodiesel produced from microalgae is an option to be considered and improved for production and use on a commercial scale.